Effects of egg white on physicochemical and functional characteristics of steamed cold noodles (a wheat starch gel food). (1st November 2022) - Bai, Jie; Dong, Mengxue; Li, Jiayu; Tian, Liangjie; Xiong, Dandan; Jia, Jie; Yang, Lu; Liu, Xuebo; Duan, Xiang
Abstract: Steamed cold noodles (SCN) is a popular wheat starch-based (gluten-free) gel food in China. However, some textural and nutritional problems are existed because of the single component (mainly starch and water), such as easy breakage, lack of toughness and high glycemic index. In this paper, egg white was introduced into SCN, and the impacts on texture, rheological properties, gel properties and functional properties of SCN were studied. The introduction of egg whites increased the hardness, chewiness, resilience, shear resistance of gel, and increased the water holding capacity of the gel from 87% to approximately 94%. At the same time, a significantly different in digestibility was seen between SCN with and without egg white. Egg whites made the whole polysaccharide gel system more compact. These results suggested that egg whites can improve the gel characteristics and functional properties of starch gel, contributing to the development of new gluten-free foods. Highlights: The SCNs with different amounts of egg white were prepared. Egg whites strengthened the textural and sensory properties of SCN. Egg whites reduced the in vitro digestibility of SCN. Egg white endowed SCN a better amino acid composition.